2002
DOI: 10.1111/0162-895x.00282
|View full text |Cite
|
Sign up to set email alerts
|

Sometimes You Feel Like a Nut, Sometimes You Don't: Citizens' Ambivalence About Abortion

Abstract: Recent research has recognized that many people simultaneously hold positive and negative attitudes about important political issues. This paper reviews the concept of attitudinal ambivalence and introduces a survey measure of ambivalence adapted from the experimental literature. An analysis of two statewide telephone surveys of Florida voters reveals that (1) a number of voters have ambivalent attitudes about abortion rights; (2) the amount of ambivalence varies according to the circumstances (elective versus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
74
0
4

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 37 publications
(30 reference statements)
4
74
0
4
Order By: Relevance
“…The construct validity of each of the different measures was assessed by comparing how well the theoretical sources of ambivalence predict each measure respectively. The findings indicate that the approach adapted from earlier work (Craig, Kane, and Martinez 2002; that forces respondents to rate their positive and negative feelings separately is the most valid if we agree that ambivalence can be defined as the simultaneous possession of positive and negative evaluations. The evidence provides support to previous research that suggested ambivalence may result when individuals have conflicting thoughts or beliefs (cognitive conflict), conflicting feelings (affective conflict), or beliefs in conflict with feelings (cognitive-affective conflict).…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…The construct validity of each of the different measures was assessed by comparing how well the theoretical sources of ambivalence predict each measure respectively. The findings indicate that the approach adapted from earlier work (Craig, Kane, and Martinez 2002; that forces respondents to rate their positive and negative feelings separately is the most valid if we agree that ambivalence can be defined as the simultaneous possession of positive and negative evaluations. The evidence provides support to previous research that suggested ambivalence may result when individuals have conflicting thoughts or beliefs (cognitive conflict), conflicting feelings (affective conflict), or beliefs in conflict with feelings (cognitive-affective conflict).…”
Section: Discussionmentioning
confidence: 70%
“…The range of scores for each of the seven items described above is -0.5 through 4.0, with intervals of 0.5 (see Craig, Kane, and Martinez 2002). A principal components factor analysis confirmed that all seven load on a single factor, and the reliability of an additive index constructed from them is very high (α = .860).…”
Section: Dependent Variablesmentioning
confidence: 89%
See 3 more Smart Citations